Pengaruh Strategic Management Accounting dalam Memediasi Pengaruh Orientasi Pasar, dan Kualitas Pimpinan terhadap Kinerja Keuangan - Christina Verawaty Situmorang; Arthur Simanjuntak (Universitas Medan Area, 2021)
The aim of the study is to identify and analyze the impact of strategic management accounting, which mediates market orientation and leadership qualities to financial performance. This research is quantitative descriptive research. Researchers use quantitative descriptive research to uncover the truth about the study's problems. Bbased on the facts and information available obtained directly from the respondent. The types of data used are primary and supporting data. The main data is obtained from respondents with direct interviews of competent respondents. Supporting data isobtained from dokumen Hotel in Medan City. The method used in data collection in the form of interviewing informants who are sources is hotel managers up to employees who work for at least 3 years. The population of this study is all hotels based on the criteria of three-, four- and five-star hotels in the city of Medan and have been established for at least 5 years. The method used is metode purposive sampling, with the number of samples obtained as many as 64 respondents. Based on the results of the study, partially Market Orientation affects Financial Performance through Strategic Management Accounting. And The Quality of Leaders influences Financial Performance through Strategic Management Accounting. Simultaneously Market Orientation and Leadership Quality have a significant effect on Financial Performance. And Market Orientation and Leadership Qualities Affect Financial Performance Through Strategic Management Accounting.